Investigation on the structural features of Zhundong subbituminous coal through ruthenium ion-catalyzed oxidation. Issue 15 (29th January 2016) - Lv, Jing-Hui; Wei, Xian-Yong; Wang, Ying-Hua; Wang, Tie-Min; Liu, Jing; Zhang, Dong-Dong; Zong, Zhi-Min
Abstract : The structural features of Zhundong subbituminous coal were investigated by RICO and subsequent analysis with a gas chromatograph/mass spectrometer and an atmospheric pressure solid-analysis probe/time of flight-mass spectrometer. Abstract : The structural features of Zhundong subbituminous coal (ZSBC) were investigated by ruthenium ion-catalyzed oxidation (RICO) and subsequent analyses with a gas chromatograph/mass spectrometer and an atmospheric-pressure solid analysis probe/time of flight-mass spectrometer (ASAP/TOF-MS). The results suggest that condensed aromatic rings linked by short polymethylene bridged linkages, long side chains, and oxygen-containing groups are predominant in ZSBC. Aliphatic bridged linkages connecting 3 aromatic rings also exist in ZSBC. Several heterocyclic carboxylic acids were produced from RICO of ZSBC. The heterocyclic moieties include tetrahydrofuran, pyridine, pyrazole, benzo[ b ]thiophene, and dithiole rings, suggesting the existence of oxygen-, nitrogen-, and sulfur-containing building blocks in ZSBC. According to analysis with ASAP/TOF-MS, a series of heavier arenecarboxylic acids were detected in the products from RICO of ZSBC and aromatic rings of the heavier arenepolycarboxylic acids include naphthalene, biphenyl, anthracene, phenylnaphthalene, and methyl(phenyl)tetrahydroanthracene, implying that ZSBC contains highly condensed aromatic rings. The existence of chlorine- and bromine-containing moieties was confirmed by the identification of chlorine- and bromine-containing species produced from RICO of ZSBC.